2012
DOI: 10.3109/08923973.2012.739175
|View full text |Cite
|
Sign up to set email alerts
|

Insertion/deletion polymorphism of the angiotensin-converting enzyme gene in lupus nephritis among Mexicans

Abstract: No association was identified between I/D polymorphisms of ACE and SLE, LN, or GMN in a Mexican population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…In support to the above reports, Zhou et al in their meta-analysis found that the polymorphic ACE gene deletion allele was a genetic risk factor for SLE and development of lupus nephritis [21]. However, our findings are in agreement with the reports by Topete-Reyes et al, who suggested that the ACE insertion/ deletion polymorphism neither influenced the incidence of lupus nephritis nor the different histopathological classes of lupus nephritis in Mexican mestizos [22].…”
Section: Discussionsupporting
confidence: 88%
“…In support to the above reports, Zhou et al in their meta-analysis found that the polymorphic ACE gene deletion allele was a genetic risk factor for SLE and development of lupus nephritis [21]. However, our findings are in agreement with the reports by Topete-Reyes et al, who suggested that the ACE insertion/ deletion polymorphism neither influenced the incidence of lupus nephritis nor the different histopathological classes of lupus nephritis in Mexican mestizos [22].…”
Section: Discussionsupporting
confidence: 88%
“…The process for selecting the studies is shown in Figure . One hundred and ninety potentially relevant records were first reviewed, and a total of 23 studies meeting the inclusion criteria were finally identified in the meta‐analysis . Among these recruited investigations, three were published in Chinese, and the others were reported in English.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a total of 27 separate comparisons were considered in the meta‐analysis involving 2718 patients and 3655 controls. Fifteen studies involved Asian populations, seven studies involved European populations, three investigations involved African populations, one study each examine South American and North American populations . Characteristics of studies discussing the correlation between ACE I/D polymorphisms with SLE are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations